Ossification of superior transverse scapular ligament - a case report - Dibya Prabha Bara; Swagatika Pradhan; Rajashree Biswal; Chinmayi Mohapatra (Wolters Kluwer Medknow Publications, 2015)
Superior transverse scapular ligament (STSL), a small ligament which bridges over the suprascapular notch bears enormous stress during shoulder movements. This causes the ligament to ossify thereby compressing the suprascapular nerve which passes beneath it. The ossification can occur partially or completely. Different shape of ossified STSL also affects the rate of compression of the nerve. Knowledge of ossified STSL may be helpful for radiologists, neurosurgeons and orthopaedic surgeons in dealing with patients of suprascapular nerve entrapment.